Do we all experience loneliness the same way? Lessons from a pilot study measuring loneliness among people with lived experience of homelessness. (30th September 2021) - Bower, Marlee; Gournay, Kevin; Perz, Janette; Conroy, Elizabeth
Abstract: Loneliness research has tended to focus on mainstream and older populations despite evidence that non‐mainstream groups, like those experiencing homelessness, may experience loneliness differently. Limited existing research indicates that (a) people who have been homeless experience loneliness as multidimensional (as a pluralistic, non‐unidimensional emotion, experienced specific to lacked relationships) and (b) mainstream loneliness scales may be inappropriate for this group. The current study piloted and appraised the feasibility the short version of the Social and Emotional Loneliness Scale for Adults (SELSA‐S) among 129 Australian adults with a lived experience of homelessness. Exploratory Factor Analysis and an observational questionnaire appraisal were used to assess factorial and content validity and showed the measure did not fit this sample as well as in mainstream samples. Removal of items that participants found difficult to comprehend/answer improved the factorial fit of the scale. In conclusion, the SELSA‐S may be inappropriate for measuring loneliness among people who have experienced homelessness. Further research needs to explore the potentially different structure of loneliness among marginalised groups so that a better understanding of loneliness can be reached.